Myricanol 5-fluorobenzyloxy ether regulation of survivin pathway inhibits human lung adenocarcinoma A549 cells growth in vitro - Guan-hai Dai; Xuan Chen; Ze-ming Ren; Chen-jie Dai; Ye-ling Tong; Ke-qun Chai (BMC, 2020)
Abstract Background This study aimed to explore the growth inhibitory effect of myricanol 5-fluorobenzyloxy ether (5FEM) and its underlying mechanisms in human lung adenocarcinoma A549 cells in vitro. Methods 5FEM was obtained by the chemical modification of myricanol with fluorobenzyloxy ether at the OH(5) position. The cytotoxicity, cell apoptosis, cell cycle, mitochondrial membrane potential (ΔΨm), scratch test, colony formation, and the expression levels of the key survivin pathway-related genes in A549 were evaluated. Results 5FEM could significantly inhibit A549 cell growth; induce cell apoptosis; increase G0/G1 population; reduce ΔΨm; inhibit cell migration and colony formation; upregulate caspase-9, P21, and Bax expression levels; and downregulate PARP, survivin, and Bcl-2 expression level. Conclusion These results enhanced our understanding of 5FEM and aid the discovery of novel myricanol derivatives as potential antitumor agents.